IMPLEMENTASI MODEL ASSURE DALAM PEMBELAJARAN DARING PADA MATA PELAJARAN BAHASA ARAB DI MI NURUL HIDAYAH - Rachma Nika Hidayati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
In the learning process, the presence of the media has a fairly important meaning. The ambiguity of the material or material presented in learning can be helped by presenting the media as an intermediary. Learning media are all tools and materials that can be used for educational purposes such as radio, television, books, newspapers, magazines, and so on. Learning media serves to enhance children's absorption and retention of learning materials because the success of learning is largely determined by two main factors, namely methods and media. The ASSURE model is one of the guidelines and planning that can help for how to plan, identify, determine goals, choose methods and materials, and evaluate. The purpose of this study was to apply the Assure model in online learning in Arabic subjects.